Patient reported symptoms in emergency health care service in patients with complete atrioventricular block. (3rd October 2022) - Sorensen, E; Moller, A; Lippert, F; Kober, L; Kragholm, K; Folke, F; Blomberg, S; Christensen, H; Torp-Pedersen, C; Bang, C
Abstract: Aim: To examine initial symptoms in emergency and medical helpline calls of patients prior to hospital admission and pacemaker implantation due to recent onset of complete atrioventricular block. Methods: In the capital region of Denmark, Copenhagen, citizens who require medical assistance can contact either the regional 24h non-urgent medical helpline 1813 or the emergency number 1–1-2 (equivalent to 9–1–1). In both services, the symptoms/purposes of the calls are registered by health professionals. We identified calls from patients who received a pacemaker due to recent onset complete AV block. Prior to analysis, symptoms were categorized as fainting, dizziness, other CNS symptoms, chest pain, other cardiac symptoms, breathing problems, trauma/exposure, unconsciousness, unclear problems, and other atypical symptoms. Results: We identified 451 calls (261 emergency calls and 190 non-emergency calls) which included information on symptom presentation prior to hospital admission due to first time diagnosis of complete atrioventricular block, that resulted in pacemaker implantation (Figure). Typical symptoms such as fainting and dizziness accounted for only 12.6% (57/451) and 13.3% (60/451), respectively. Chest pain (13.6%, 61/451) and other cardiac symptoms (5.3%, 24/451) accounted for roughly one in five patient complaints. Across both service types, patients >80 years (median age) was more likely to call for help due to trauma/exposure, while complaints of fainting trended towards younger patients and the 1-1-2 emergency number. Median time from first call to pacemaker implantation was 2–3 days for fainting, dizziness, and chest pain, compared to 6–8 days for other CNS symptoms and other atypical symptoms (Table). Conclusion: Typical symptoms such as fainting and dizziness accounted for only 13% in patients with complete atrioventricular block. Instead, these patients presented with a wide variety of initial symptoms, including chest pain, breathing problems, unclear problems, or trauma. Finally, symptom presentation seemed to affect the time to pacemaker implantation. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Danish Heart Foundation